Modification of the Local Drink Wedang Tomboan as a Gastronomic Tourism Attraction in Ngawonggo Village, Malang Regency - Khubiyah, Visda Imammatul; Afriani, Welly Ayu; Turgarini, Dewi (Journal of Tourism Education, 2023)
Ngawonggo Village, Malang Regency, is a tourism destination for the Petirtaan Ngawonggo ancient site which is visited by tourists. Based on the data obtained, it has been visited by domestic and foreign tourists. The beverage needs of these tourists are met by serving modern drinks originating from outside the destination area. Meanwhile, the local drink Wedang Tomboan, which comes from raw materials around this area, requires modifications so that the taste, texture, color, presentation and packaging can be accepted by domestic and foreign tourists. Apart from that, there is another problem, namely that this wedang can become a culinary tourism attraction that attracts tourists. The aim of this research is to find modifications to Wedang Tomboan beverage products with organoleptics and packaging that can attract tourists as a culinary tourism attraction that can sustainably prosper destinations in the area. The method used is qualitative. The organoleptic test results show that the best sample has the highest level of liking, namely F2. Where guests prefer the addition of ginger and secang fiber formulations in Wedang Tomboan to add a spicy taste and a more attractive color.